Pharmacophore‐based discovery of inhibitors of a novel drug/proton antiporter in human brain endothelial hCMEC/D3 cell line. (13th October 2015) - Chapy, Hélène; Goracci, Laura; Vayer, Philippe; Parmentier, Yannick; Carrupt, Pierre‐Alain; Declèves, Xavier; Scherrmann, Jean‐Michel; Cisternino, Salvatore; Cruciani, Gabriele
Abstract: Background and Purpose: An influx drug/proton antiporter of unknown structure has been functionally demonstrated at the blood–brain barrier. This transporter, which handles some psychoactive drugs like diphenhydramine, clonidine, oxycodone, nicotine and cocaine, could represent a new pharmacological target in drug addiction therapy. However, at present there are no known drugs/inhibitors that effectively inhibit/modulate this transporter in vivo . Experimental Approach: The FLAPpharm approach was used to establish a pharmacophore model for inhibitors of this transporter. The inhibitory potency of 44 selected compounds was determined against the specific substrate, [ 3 H]‐clonidine, in the human cerebral endothelial cell line hCMEC/D3 and ranked as good, medium, weak or non‐inhibitor. Key Results: The pharmacophore model obtained was used as a template to screen xenobiotic and endogenous compounds from databases [Specs, Recon2, Human Metabolome Database (HMDB), human intestinal transporter database], and hypothetical candidates were tested in vitro to determine their inhibitory capacity with [ 3 H]‐clonidine. According to the transporter database, 80% of the proton antiporter inhibitor candidates could inhibit P‐glycoprotein/MDR1/ABCB1 and specificity is improved by reducing inhibitor size/shape and increasing water solubility. Virtual screening results using HMDB and Recon2 for endogenous compounds appropriately scored tryptamine as an inhibitor. Conclusions and Implications: The pharmacophore model for the proton‐antiporter inhibitors was a good predictor of known inhibitors and allowed us to identify new good inhibitors. This model marks a new step towards the discovery of this drug/proton antiporter and will be of great use for the discovery and design of potent inhibitors that could potentially help to assess and validate its pharmacological role in drug addiction in vivo .